Chronologic distribution of the Glyptodontidae (Mammalia, Cingulata) recorded in the Villavil-Quillay Basin, Catamarca, Argentina - Núñez Blasco, Alizia (2020)
The present work shows the precise age of some of the most complete fossil specimens belonging to Glyptodontidae exhumed in the Villavil-Quillay basin (Department of Belén, Catamarca Province, Argentina). Thisnspecimens were integratedinto an ideal stratigraphic profile of the Santa María Group outcrops in this area, adding information of radiometric dating by K40/Ar40 and Ar40/Ar39 isotopes performed by other authors. Concerning Doedicurinae, the genus Eleutherocercusshows a distribution of remains along the sequence, from 7.14±0.05 Ma to levels after 3.66±0.05 Ma; the geological record shows a higher concentration of fossils in the Zanclean, the lowest stage of the Pliocene, being also the taxon with the latest records together with the genera Stromaphorus and Phlyctaenopyga. Oldestrecord of the genus Eosclerocalyptus is close to 7.14±0.05 Ma, but remaining fossils were concentrated in levels ranging from 5.64±0.16 Ma to 5.3±0.2 Ma, corresponding to the limit between the Messinian (the final stage of the Miocene)and the Zanclean (lowest Stage of the Pliocene). In turn, fossils of the genera Stromaphorus and Phlyctaenopyga are only recorded between ca. 6Ma. to 3.66±0.05 Ma, so far limited for the late Messinian to all Zanclean stage. Obtaining a precisetime frame for these fossils will allow us the possibility of generating a much more reliable information in future in that concerning paleobiological,taxonomic and evolutionary issues still to be resolved for Glyptodontidae diversityof the Argentinian North Western region. Also, will allow a more accurate comparison with fossil remains of glyptodons of other areas of South America of equivalent age.